Research progress on medication literacy of elderly cancer patients during oral chemotherapy (老年肿瘤患者口服化疗药物期间药物素养研究进展) - LIU Yin (柳吟); SHI Ruchun (施如春); HUANG Jun (黄君); ZHAO Hongxia (赵红霞); QIU Minyan (邱敏燕); SHEN Xiaoyan (沈晓燕) (中西医结合护理)
Drug therapy is the main treatment for elderly cancer patients. Given the unique characteristics of elderly patients with cancer, including aging and underlying comorbidities, inadequate medication literacy not only decreases medication adherence but may also lead to adverse drug events. This study provides a review of the current status, influencing factors and intervention strategies related to medication literacy during oral chemotherapy in elderly cancer patients. The aim is to offer insights for enhancing medication literacy and ensuring medication safety during oral chemotherapy in elderly cancer patients. (药物治疗是老年肿瘤患者主要的治疗方式。老年肿瘤患者群体特殊, 药物素养不足不仅会降低其用药依从性, 甚至可能导致用药不良事件的发生。本研究就老年肿瘤患者口服化疗药物期间的药物素养的概念、现状、评估工具、影响因素及干预策略等方面进行综述, 旨在为提高老年肿瘤患者口服化疗药物期间的药物素养、保障用药安全提供参考。)